Studi Fenomenologi Tentang Makna Panggilan dan Kebermaknaan Hidup Caregiver Formal Lansia di Panti Wredha - Dhini Kusuma Wardhani; Rulita Hendriyani (Jayapangus Press, 2026)
The growing elderly population is directly proportional to the increasing demand for caregivers. This role presents unique challenges, including low financial rewards and a demanding workload. Despite these pressures, many caregivers choose to persist in their roles for years. A key factor strengthening this commitment is an externally focused calling, which serves as a moral commitment to providing tangible benefits to the lives of the elderly. This study aims to explore the meaning in life among formal caregivers for the elderly who experience their profession as a form of calling. Using a qualitative phenomenological approach, the study involved two caregivers with more than six years of experience and two significant others as additional informants. Data were collected through in-depth interviews and analyzed using Interpretative Phenomenological Analysis (IPA). The findings reveal five major themes: (1) calling as the foundational motivation for becoming a caregiver; (2) the caregiving process as a pathway to discovering life meaning; (3) self-transformation through caregiving experiences; (4) emotional closeness and interpersonal bonds with the elderly; and (5) the emergence of pride as an expression of meaningful living. These findings confirm that meaning in life is formed through emotional, relational, cognitive, and spiritual experiences within the caregiving process: ultimately, finding meaning in this work enables individuals to avoid existential vacuum and enhance their existential resilience.